Marble sculptures from the imperial palace in Sirmium - Popović Ivana (Starinar, 2006)
Few fragments of marble sculpture have been found in the course of the archaeological excavations conducted in Sirmium between 2003 and 2005 at site 85 which is believed to be part of the imperial palace complex. The most important are two almost completely preserved heads of deities. The head of a young person made of milky white, fine-grained marble of exceptionally fine texture from Pentelicon was found under the Late Roman floor in room 7 of the residential structure. The sculpture, of exceptional quality, is from the second half of the 1st century and represents a deity, most probably Venus or Apollo. Another head made of Carrara marble, from the 4th century, was found in a secondary position and on the basis of its mural crown is identified as the Tyche of Sirmium.